On the normal approximation for weakly dependent random variables - Sunklodas, Jonas (Lietuvos matematikos rinkinys, 2005)
In this report, we present the estimates of the difference |Eh(Zn) − Eh(N)|, where Zn is a sum of n centered and normalized random variables which satisfy the strong mixing condition (without assuming a stationarity), and N is a standard normal random variable for the function h: ℝ → ℝ which is finite and satisfies the Lipschitz condition. In a particular case, the obtained upper bounds are of order O(n−1/2).
Keywords: normal approximation; random variables